Cross Spectrum Switching in Mobility Scenario for Signaling Overhead Minimization in HetNet (Global Journals of Research in Engineering, 2016)
The issue of mobility concern in heterogeneous network is addressed in this paper. The coding approach of spectrum utilization and signal effort in user mobility in heterogeneous network is been made. New coding approach of spectrum utilization in concern with resource utilization and signaling overhead is focused. New approach of spectrum utility level is been made to overcome the issue of signaling overhead in spectrum utilization in Het Net. For achieving the objective of fairness in heterogeneous network under mobility constraint, multi objective coordination approach for optimal resource utilization is proposed. The resource utilization problem is defined by the effective spectrum utilization among network users minimizing the signaling overhead. The simulation observations developed shows an improvement in significant resource utilization in compare to conventional approaches.
Keywords: cross spectrum utilization; resource sharing; signaling overhead; spectrum allocation